PENGARUH PENERAPAN COURTYARD PADA KAFE KINERUKU TERHADAP KENYAMANAN PENGUNJUNG - Surya, Felicia; Darmayanti, Tessa Eka (Aksen : Journal of Design and Creative Industry, 2024)
Green Open Space (RTH) is an open area that allows plant growth both naturally and through deliberate planting. The existence of green open space is now an important thing to have in a public interior facility, one of which is the application of a courtyard. Therefore, it is necessary to increase public awareness and understanding regarding the importance of utilizing green open spaces, especially in public facilities. This research aims to investigate the effect of courtyard implementation on the comfort level of visitors at a cafe located in Bandung, Indonesia. This research will apply the use of descriptive qualitative methods with a phenomenological approach and spatial atmosphere theory. This research will use field observation techniques, physical documentation and interviews with visitors. The results of the research will show conclusions about the comfort of Kineruku cafe visitors regarding the implementation of courtyards in cafes. The results of this research are information regarding the comfort level and preferences of visitors regarding the application of courtyards in cafe interiors in the city of Bandung. It is hoped that this research can provide a valuable insight that align with the Bandung City Government's commitment to maintaining green open spaces (RTH), namely the Draft Regional Regulations on Regional Spatial Planning (RTRW) for the City of Bandung 2022-2042.